Factors Affecting The Business Performance of Small and Medium Enterprises in Xay District, Oudomxay Province - keomoukda, bounthavy; CHANTHAVONE, Thongphanh; PHOUNNALY, Phayvanh (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
The purposes of this study were: 1) to assess the level of business performance of small and medium enterprises in Xay district, Oudomxay province; and 2) Factors affecting the business performance of small and medium enterprises in Xay district, Oudomxay Province. The Population and Sample consisted of 176 entrepreneurs in Xay district, Oudomxay province. Data were collected using questionnaires, and statistical methods including frequency, percentage, mean, standard deviation and multiple regression were used for analysis. The research findings were that entrepreneurs in Xay district have a high level of business performance in their small and medium enterprises. Their business performance was ranked from highest to lowest score as follows: financial performance, learning and growth, internal process, and customer performance. Factors affecting the business performance of small and medium enterprises in Xay district, Oudomxay province, consist of seven factors such as: marketing transformation, financial transformation, people transformation, economic, technological, environmental, and legal factor at a statistical significance level of 0.05. These factors were found to be statistically significant at the 0.05 level, and the multiple regression model achieved a prediction accuracy of 67.7% (R2=0.6770).